2017
DOI: 10.1093/pm/pnx149
|View full text |Cite
|
Sign up to set email alerts
|

Review of Factors, Methods, and Outcome Definition in Designing Opioid Abuse Predictive Models

Abstract: We identified variables used to predict opioid abuse from electronic health records and administrative data. Medication variables are the recurrent variables in the articles reviewed (33 variables). Age and gender are the most consistent demographic variables in predicting opioid abuse. Overall, there is similarity in the sampling method and inclusion/exclusion criteria (age, number of prescriptions, follow-up period, and data analysis methods). Intuitive research to utilize unstructured data may increase opio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…In recognition that various comorbidities can influence general healthcare utilization, a number of comorbidities were identified based on a medical visit with a corresponding ICD-9 code. A recent systematic review identified nine predictive models for determining opioid abuse, and the majority were based on diagnosis codes (ICD-9) (Alzeer et al 2018 ). Specific details for how these variables were extracted and their relevance to prognosis in individuals with musculoskeletal outcomes have been published (Rhon et al 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…In recognition that various comorbidities can influence general healthcare utilization, a number of comorbidities were identified based on a medical visit with a corresponding ICD-9 code. A recent systematic review identified nine predictive models for determining opioid abuse, and the majority were based on diagnosis codes (ICD-9) (Alzeer et al 2018 ). Specific details for how these variables were extracted and their relevance to prognosis in individuals with musculoskeletal outcomes have been published (Rhon et al 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…25,26 Reviews also examined predictors of opioid misuse and abuse, and overdose, but predictors may differ for LTOT. [27][28][29][30][31][32] Little is known about the criteria used to define LTOT for research purposes, and there has been no synthesis of the risk factors associated with transition from short-term opioid therapy to LTOT. Without an understanding of the criteria or the predictors of LTOT, it is difficult to understand the strengths and limitations regarding the evidence on the risk of LTOT, distinguish between episodic and longterm opioid use, and monitor the prevalence and incidence of LTOT.…”
Section: Korff and Colleagues On Ltot Clinical Guidelines Define Ltomentioning
confidence: 99%
“…However, in these studies, arthritis, chronic pain, tobacco use, drug disorders, and mental health disorders were consistently identified as risk factors for LTOT, many of which are similar to the risk factors associated with misuse, abuse, and overdose. [27][28][29][30][31][32] Finally, only three predictors examined prior opioid prescriptions, suggesting limited evidence on how initial prescribing may lead to LTOT. In a study not included in this review because it included pediatric patients, the number of fills and total dose during the first month of opioid use were associated with greater risk of LTOT.…”
Section: /1002 = 57%mentioning
confidence: 99%
See 1 more Smart Citation
“…"opioid overdose" vs. "opioid abuse") and population inclusion criteria (minimum medication day's supply or number of opioid prescriptions) may alter the ability to achieve consensus on the problem definition and the population that requires intervention (15). Despite these differences, the International Classification of Diseases (ICD) is a standard method used by health care providers to diagnose opioid use disorder, overdose, abuse, and dependence (which we will refer to in this study as Opioid Use Problems or OUP).…”
Section: A Backgroundmentioning
confidence: 99%